The Influence of Country of Origin, Product Involvement, and Halal Brand Awareness on the Purchase Decision of Samyang Instant Noodles in Banda Aceh City - Hawa, Aqlima Putri; Nizam, Ahmad; Umuri, Khairil (Universitas Syiah Kuala, 2025)
This study aims to examine the influence of Country of Origin, Product Involvement, and Halal Brand Awareness on the purchase decision of Samyang instant noodles in Banda Aceh. Data were collected through questionnaires distributed to 170 respondents who had previously purchased Samyang products. The sampling technique used was purposive sampling combined with proportional sampling. Data analysis was conducted using multiple linear regression. The results show that both partially and simultaneously, Country of Origin, Product Involvement, and Halal Brand Awareness have a significant influence on purchase decisions. The Country of Origin variable indicates that positive perceptions of a products country of origin can increase consumer trust. Product Involvement shows that higher consumer engagement with a product increases the likelihood of purchase. Halal Brand Awareness demonstrates that consumer awareness of halal labels influences purchase decisions, especially in predominantly Muslim regions. These findings are expected to contribute to a better understanding of consumer behavior toward imported products and can serve as a reference for businesses in designing marketing strategies that align with the preferences and values of consumers in the research area.